Nursery management in onion - Khade, Yogesh P; Thangasamy, A; Ghodke, Pranjali (Indian Horticulture, 2019)
In India, onion is the most important crop mainly planted by two methods, viz. direct seeding and transplanting. The area under direct seeding is less (10- 15%) compared to transplanting (85-90%). In onion production, nursery management is the most important practice to produce healthy seedlings suitable for transplanting in kharif, late-kharif and rabi season. Since onion is raised by raising nursery and transplanting of nursery, proper care must be taken for producing healthy seedlings. Therefore, site selection, soil and climatic conditions, nursery bed preparation, seeds and sowing, water management, weed management, nutrient management, use of shade and plant-protection measures should be considered properly.